Competências do professor no processo de ensino-aprendizagem de língua estrangeira - Consolo, Douglas Altamiro [UNESP]; Porto, Cristina Francisca de Carvalho [UNESP] (My University, 2011)
In this article we discuss competences demanded from the foreign language teacher for him or her to perform in the teaching-learning process efficiently. Our reflections are based mainly on Paulo Freire (2001), Philippe Perrenoud (2000), Edgar Morin (2003), Maurice Tardif (2002) and Almeida Filho (1999), providing, in this way, a reflective dialogue among studies that focus on teachers’ competences. The main objective is a better understanding of the necessary knowledge about teaching practices so that foreign language teachers’ actions can meet the needs of education at present. We expect to highlight important issues in the development of the aforementioned competences, and suggest that their development can contribute for better language teaching.

Neste artigo objetiva-se refletir sobre as competências necessárias ao professor de língua estrangeira para que este atue eficazmente no processo de ensino-aprendizagem. Para fundamentar esta discussão tomam-se como base teórica as obras de Paulo Freire (2001), Philippe Perrenoud (2000), Edgar Morin (2003), Maurice Tardif (2002) e Almeida Filho (1999), além de outros estudos acerca do tema, realizando assim uma discussão entre diferentes textos que abordam esta mesma problemática. O principal objetivo é compreender um pouco mais sobre os saberes docentes necessários a uma boa atuação do professor de línguas estrangeiras na atualidade. Esperamos, com tais reflexões, salientar a importância das competências docentes para o processo de ensino-aprendizagem de língua estrangeira e, consequentemente, para uma prática docente mais qualificada.
Teachers' competences in the process of foreign language learning and teaching
Keywords: competências do professor; ensino/aprendizagem de línguas; formação continuada; formação de professores; língua estrangeira; língua francesa; competences; teacher development; foreign language; teaching; practice